Chemical and genomic analyses of a marine-derived Streptomyces sp. V17-9 producing amino acid derivatives and siderophores - Kim, Da-Eun; Hong, Sung-Chul; Yang, Yoonyong; Choi, Jaeyoung; Park, Jin-Soo (Frontiers in Marine Science, 2022)
Streptomyces, the largest genus in Actinobacteria, has been known as a chemically prolific bacterial group producing pharmaceutically important small molecules. Various endeavors have been made to discover novel secondary metabolites from strains inhabiting diverse environmental niches. In our course of collecting bacterial strains to discover biologically active molecules, a marine-derived Streptomyces sp. V17-9 was isolated from a seagrass collected from a beach on Côn Đảo, Vietnam. Phylogenetic and genomic analyses suggested the possibility that this strain might form a new taxonomic group with a few closely related unclassified strains. The genome sequence of strain V17-9 was predicted to have 20 putative biosynthetic gene clusters. A chemical investigation identified amino acid derivatives (N-acetyltryptamine, N-acetyltyramine, and 6-prenyltryptophol) and siderophores (desferrioxamine E and spoxazomicin A) from culture extracts, linking gene clusters with actual productions. In particular, prenylated indole compounds were enhanced in production as part of metabolic conversion under supplement with ferric ions. Sequence similarity networks for indole and siderophore gene clusters showed their diversity and complexity in the genus Streptomyces. Phylogenomic analysis of gene cluster for 6-prenyltryptophol suggested strains of genomic potential for production of such compounds. They also suggested how these gene clusters may have shaped the biosynthesis of natural products. Chemotaxonomic profiling coupled with genome analysis would provide new insights into comparative studies on Actinobacteria producing prenylated indoles and siderophores.